Developing precision medicine using scarless genome editing of human pluripotent stem cells. (August 2018) - Steyer, Benjamin; Cory, Evan; Saha, Krishanu
Abstract : Many avenues exist for human pluripotent stem cells (hPSCs) to impact medical care, but they may have their greatest impact on the development of precision medicine. Recent advances in genome editing and stem cell technology have enabled construction of clinically-relevant, genotype-specific "disease-in-a-dish" models. In this review, we outline the use of genome-edited hPSCs in precision disease modeling and drug screening as well as describe methodological advances in scarless genome editing. Scarless genome-editing approaches are attractive for genotype-specific disease modeling as only the intended DNA base-pair edits are incorporated without additional genomic modification. Emerging evidentiary standards for development and approval of precision therapies are likely to increase application of disease models derived from genome-edited hPSCs.